Oil palm leaf fibre and its suitability for paper-based products - Mohd Kassim, Angzzas Sari; Mohd Aripin, Ashuvila; Ishak, Nadiah; Zainulabidin, Muhd Hafeez; Abang Zaidel, Dayang Norul Fairuz (Asian Research Publishing Network (ARPN), 2016)
Due to the shortage of wood as origin materials for paper-based production, agro-residue materials have been explored in the quest of finding the best alternative fibre. Oil palm leaf (OPL) is one of agro-residue that has potential due to its comparable characteristics with wood fibre. Studies on chemical compositions, fibre morphology, and mechanical property of OPL have been carried out aiming to evaluate its potential as a substitute raw material for pulp and paper-based production. The chemical compositions were analysed according to the TAPPI standard, Kurscher-Hoffner and chlorite methods accordingly. The mechanical property (tensile, tearing and bursting strengths) were determined as described in TAPPI test methods. Fibre dimensions were determined using Franklin method and analysed under the optical microscope. The content of cellulose in the OPL is determined to be 43.8%. Although, this result is lower than wood fibre (53%), OPL has higher hemicellulose content (36.4%) than the wood fibre (27.5%). In addition, the lignin content (19.7%) of OPL is in the low range of those in wood resources (18 - 25%). These parameters are important components to produce good quality pulp and will provide high mechanical strength of the paper-based products. The measured fibre length of oil palm leaf (1.13 mm) is shorter than the wood fibre (1.90 mm). Meanwhile, the mechanical property of OPL showed lower indexes than wood resources, however, tear (1.80 mN.m2/g) and burst (0.95 kPa.m2/g) indexes of OPL are higher than other published and successful wood resources (Eucalyptus). Based on the analyses, the oil palm leaf is indeed a suitable alternative of raw material for pulp and paper-based industries.